Pengaruh Kecukupan Modal dan Inefisiensi terhadap Profitabilitas Bank Pembangunan Daerah di Indonesia - Amalia Rahma Tiara Putri; Muhammad Iqbal Pribadi; Yulia Tri Kusumawati (MES Bogor, 2024)
The purpose of this study is to examine whether capital adequacy and inefficiency affect the profitability of regional development banks in Indonesia for the period 2015-2022. The data analysis technique uses panel data regression. The population used is 26 Regional Development Banks listed in the Regional Development Bank Association. The sample consisted of 24 BPD banks with 192 observation data, which were carried out by purposive sampling. In this study, capital adequacy is measured using Capital Adequacy Ratio (CAR), Inefficiency is measured by Operating Expenses Operating Income (BOPO) and profitability is measured using Return On Asset (ROA). The results showed that capital adequacy has a significant positive effect on profitability, and inefficiency has a significant negative effect on profitability